Factors affecting implementation of patient-reported outcome and experience measures in a pediatric health system - Erin McCabe; Sarah Rabi; Sumedh Bele; Jennifer D. Zwicker; Maria J. Santana (SpringerOpen, 2023)
Plain English summary Patient-reported outcome measures are standardized questionnaires that ask patients about their health and well-being and are useful for tracking patient progress and outcomes of care. Patient-reported experience measures ask patients about their experiences while receiving care and are useful for quality improvement and experience research. Clinicians can use them to help identify patients' needs, monitor a person's health status, and to give extra information that helps with planning treatment. These measures also provide data that health services can use to understand whether their programs are helpful from the patients' perspective. We know that using these measures is beneficial, but there are many challenges to overcome before they are used consistently in a health system. In pediatrics there are special considerations, like whether a caregiver or child should be answering the questions, or whether a parent should be able to see their child's answers. In this study, we interviewed people in the pediatric health system who are successfully using patient-reported outcome and experience measures about the challenges they face and the strategies they find helpful for using these measures. This information will be helpful for people who are planning to start using these measures in pediatric health care.